PERFORMANCE AND TECHNICAL FEASIBILITY STUDY OF WIND TURBINE FOR ACHIEVING ENERGY INDEPENDENCE: A CASE STUDY IN BANGOWAN TOURIST VILLAGE, INDONESIA - Herraprastanti, Eva Hertnacahyani; Kiono, Berkah Fajar Tamtomo; Haryanto, Ismoyo; Muchammad (Journal of Applied Engineering Science, 2025)
This study evaluates the feasibility of wind energy for energy independence in Bangowan Tourist Village, Central Java, Indonesia, using real-time monitoring via the ThingSpeak Internet of Things (IoT) platform. The novelty of this work lies in combining IoT-based real-time monitoring with Archimedes turbines to assess renewable energy feasibility in a rural tourist village context. The average wind speed was 6.04 m.s-1. A single Archimedes turbine produced 5,284 Wh/day, while two turbines generated 10,568 Wh/day, equal to 32.95% of the 32,075 Wh daily demand. Regression analysis showed a modest but significant correlation between wind speed and power (p = 0.043; R² = 0.049), while Tip Speed Ratio–Coefficient of Performance (TSR–Cp) analysis revealed a strong relationship (R² = 0.867). The most effective configuration combined two turbines, 2 kWp photovoltaic (PV), and a 5 kVA generator set (genset) operating 4 h/day, achieving 108.81% adequacy at ~56 million Indonesian Rupiah (IDR). Results confirm that small-scale wind is feasible if integrated into modular hybrid systems with IoT monitoring for reliable, cost-effective rural electrification.
Keywords: archimedes wind turbines, electricity consumption, renewable energy, thingspeak, tourist village